Ethics at workplace: true-four handed dentistry vs conventional method - Mohd. Kenali, Norzaiti; Sukmasari, Susi; Taib, Ibrahim Adham; Ismail, Isza Fariha (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Dental team is a profession which serves patients’ treatment need, but in a same way, their physical and mental health needs to be preserved. The practice is applied by using correct method to protect their body as an amaanah given from Allah (s.w.t). True-four handed (TFH) dentistry is ergonomically the most favorable method in terms of time and efficiency. It minimize undesirable verbal and body movements, thus protecting physical well-being of the operating team. The purpose of this study was to determine the number of TFH dentistry applied and to compare the treatment time and body movement between conventional FH and TFH dentistry among dental clinician in Kulliyyah of Dentistry IIUM. The study was conducted as a cross sectional and quasi experiment among 60 operators as participants. Observation of TFH dentistry practice was conducted and results were recorded. Six groups, consist of twelve dental students were trained with TFH dentistry application in terms of instruments and equipment, layout and procedure. Treatment time and body movement were measured and the statistic was generated using SPSS version 16. Pre and post training results were compared by using k-related sample test. From the observation, 100% of the 60 operators had an ergonomics dental instruments and equipment. Among all, 60% of the participants had assistants. Only 6.7% of the operators with assistant (four-handed) communicated non-verbally. In terms of positioning, 68.3% and 45% of the operators and assistants were sat in right position respectively. Whereas, only 11.7% of the dental team used the transfer zone correctly. There was significant difference in treatment time between pre and post training (p=0.02). There was statistically significant difference for Class II, III and Class IV body motion of the dental teams, pre and post TFH training (p<0.05). Hence, the effectiveness of TFH dentistry application in reducing treatment time and body movement was proven. More training is required among the dental practitioners to be able to practice a safe dentistry.